BIEN COMÚN - Trigo, Pedro (ITER Revista de Teología, 2026)
-- Let us analyse the common good as an alternaive and positive strategy, in the context of international and national reality. This reflexion obviously presents an opposite position to main direction or power direction. The global tendencies are very strong and oriented towards a radical individualism and to capital production at any cost. Those who choose an alternative behaviour, need to be very consisten! especially in terms of complete freedom. They must look for personal performance in the context of the existing structure, and not depending on others . .